IMPROVING STUDENTS’ MONOLOG PERFORMANCE THROUGH A NARRATIVE VIDEO - Ali Muttaqin Syurayanto (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
Monolog is one of the speaking skills that should be mastered by the students in learning a language. This skill needs many criteria that should be mastered by any speaker. There are some components in monolog performance that show whether someone meets the criteria of being success in performing his/her monolog or not. They include body language, grammar, pronunciation, fluency, speed etc. Though, before performing their monolog they have been given a simple story read in the classroom, the result of their monolog are far from being good enough. Their drawbacks can be analyzed that they are lack of getting exposed from English activities that support their performance. They can be in form watching film or video or lack of stimulus to develop their English skill performance. To improve their skill, narrative video is used to let them have more opportunity to improve their monolog. The method shows that their performance increases after they are given an independent task to watch a narrative video several times.